PENGGUNAAN METODE TIME TOKEN ARENDS UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK KELAS IV SD NEGERI 015 SUNGAI RUKAM - Yenidar Yenidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This study aims to describe the learning activities and improve learning outcomes Indonesian language through time token arends learning method on students class IV SD Negeri 015 Sungai Rukam Kecamatan Enok. From the research result, it can be seen that Time Token Arends method can improve the speaking skill in Indonesian language subjects students class IV SD Negeri 015 Sungai Rukam Kecamatan Enok. This is indicated by the results of the study seen from the average class on the initial test before the class action was done only for 59.3 with a result of completeness of 28%. Then after the action on cycle I the average value of students increased to 73.6 with a percentage of completeness of 48%. Although there is an increase, but still has not reached the predetermined criteria of learning completeness, so it must optimize again the learning process in cycle II which gets an average value of 84.1 with a percentage of completeness of 86%.